A retrospective study on the correction of distal arthrogryposis with a progressive extension brace - Zhou, Jiateng; Zhang, Tong; Wang, Zhibo; Li, Dongdong; Wu, Xin; Yu, Qinyuan; Wang, Bin (Frontiers in Pediatrics, 2024)
Purpose: Camptodactyly, clasped thumb and windblown hands represent distinctive features of distal arthrogryposis (DA). Current therapeutic interventions often yield suboptimal effect with predisposition to relapses and complications. This study explicates a corrective approach involving progressive extension brace for the management of DA and evaluates its clinical outcomes.Methods: Progressive extension braces were used between 2015 and 2023 in 32 DA patients with an average follow-up of 4.8 years. Patients were stratified by age: 0-1 year, 1-3 years, 3-7 years, and above 7 years. Correction of camptodactyly was assessed based on the total active movement (TAM) of metacarpophalangeal joints (MPJ) and proximal interphalangeal joint (PIPJ) and extensor lag of PIPJ. Clasped thumb correction was evaluated using the thumb to index finger metacarpal angle (M1M2 angle) and the degree of deviation at the first MPJ (M1P1 angle). Quality of life for the children was measured using PedsQL 4.0, while parental satisfaction was gauged using the FACE questionnaire.Results: Earlier intervention with progressive extension brace yielded superior corrective results. Infants aged 0-1 year and toddlers aged 1-3 years achieved average TAM of 152° and 126° after correction, however, TAM of patients older than 3 years decreased significantly with the same treatment. Infants and toddlers with DA showed improvement in average extensor lag from 46° to 6°. The M1M2 angle increased from an average of 38° to 65°, with the M1P1 angle decreasing from an average of 43° to 5°. After the treatment, average PedsQL scores of 94.7 (parent-report) and 89.3 (child-report) were achieved. Among the 32 parents, 24 expressed high satisfaction,5 and 3 expressed moderate and fair satisfaction respectively. The early, progressive and consistent use of extension brace significantly improved joint mobility and corrected camptodactyly and clasped thumb. It can be an effective approach in addressing hand deformities in patients with DA.